Answer:
5/4
Step-by-step explanation:
Answer:
12°, 78°, 90°
Step-by-step explanation:
let the third angle be x then the second angle is 7x - 6
The sum of the 3 angles in a triangle = 180°
Sum the 3 angles and equate to 180
x + 7x - 6 + 90 = 180, that is
8x + 84 = 180 ( subtract 84 from both sides )
8x = 96 ( divide both sides by 8 )
x = 12
Thus second angle = 12° and third = 7(12) - 6 = 84 - 6 = 78°
The 3 angles are 12°, 78° and 90°
X(^-1)^7=x^6
7(c^1)^2/3=7(c)^2/3
(m^2n^3)^-3=1/m^6n^9
Answer: 2![\frac{1}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B10%7D)
Step-by-step explanation:
2.1 is the same as 21/10
which will give 2![\frac{1}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B10%7D)